Tricycles and Their Impacts on Air Pollution within Uyo urban South-eastern Nigeria - Ebong, Godwin Asukwo; Etuk, Helen Solomon; Ambrose, Idongesit Sunday (Journal of Nepal Chemical Society, 2025)
Globally, vehicular emissions contribute significant levels of contaminants into the air. Despite the contributions by tricycles to the contamination of the air, the contamination of air is mostly linked to vehicles. Hence, this work examined the contributions of tricycles to air pollution within Uyo Urban, Nigeria. Major tricycle parking bays at Akpandem and Itam Markets, Etuk Street Market, Udi Street by Ikot Ekpene Road, Ikpa Road by University of Uyo Gate, Urua Ekpa, Ekom Iman, and Shelter Afrique Junctions were designated for this research. Portable air quality monitors were used to quantify the concentrations of NO2, SO2, H2S, CO, CO2, and PM2.5 at these locations. Results obtained showed the following mean concentrations 0.43±0.07 ppm, 0.55±0.09 ppm, 0.22±0.09 ppm, 7.25±2.37 ppm, 890.06± 300.26 ppm, and 208.72±250 µg/m3, respectively. The mean concentrations of NO2, SO2, CO, and PM2.5 were higher than their recommended safe limits by the Federal Environmental Protection Agency (FEPA), while H2S and CO2 were within their safe limits. The air quality index (AQI) analysis revealed that, NO2 and PM2.5 belong to the hazardous class, SO2, H2S, CO, and CO2 belong the class unhealthy for the sensitive class. Principal component analysis (PCA) established that, emissions from tricycles were the principal source of air contaminants determined at the studied locations. The outcome of the study confirmed that, green plants can reduce air contaminants. The study substantiated those tricycles can release significant levels of obnoxious substances into the air.